Links between emotion perception and social participation restriction following stroke. (January 2014) - Cooper, Clare L.; Phillips, Louise H.; Johnston, Marie; Radlak, Bogumila; Hamilton, Steven; McLeod, Mary Joan
Abstract Objectives: Stroke can cause impairment in emotion perception, but the social consequences of these problems have not been explored to date. In a group of patients with stroke, this study investigated whether difficulties in emotion perception related to social participation and quality-of-life. It also assessed whether these relationships remained significant when controlling for activity limitations. Method: Individuals 1 year post-stroke (n = 28) and control participants (n = 40) were assessed on emotion perception across different modalities. Activity limitations, social participation, and multiple domains of quality-of-life were assessed in patients. Results: Participants with stroke were impaired on emotion perception compared to controls. Emotion perception problems in stroke were significantly correlated with social participation and psychological aspects of QoL, but not with activity limitations. Conclusions: The strong relationships of emotion perception with social participation and psychological aspects of QoL following stroke may have implications for post-stroke outcomes.